Implementation of the Pancasila Student Profile Strengthening Project in Developing Creativity of Elementary School Students - Nunung Purwanti; Fitri Indriani (Jurnal Elementaria Edukasia, 2024)
Creativity is a new idea or imagination in creating something. This creativity is a person's ability to create new things that are developed from existing ideas or ideas that arise from their own minds. Creativity must be developed from an early age, especially during school so that there is always a renewal that is created. Increasing this creativity can be done in strengthening the values of Pancasila and entrepreneurship projects. This study examines the role of the Pancasila Student Profile Strengthening Project in fostering creativity among elementary school students through entrepreneurship initiatives. Conducted at SD Muhammadiyah Noyokerten, students engaged in various activities such as plasticine making, waste management, and healthy sandwich preparation, integrating practical skills with conceptual learning. This holistic approach aims to empower students to be creative, innovative, and environmentally conscious, contributing positively to their communities. The learning method used is descriptive qualitative which describes projects using a variety of materials and techniques to support practical and conceptual learning. The activities cover a range of topics, including flour plasticine making, plastic waste management, healthy sandwich making, and fruit ice and fruit satay making. Through these activities, students are not only introduced to practical skills, but also encouraged to understand important issues such as environmental sustainability and healthy eating. The overall conclusion is that this learning empowers students to become creative, innovative and environmentally conscious individuals, with a positive impact on their daily lives and the community around them.